2002
DOI: 10.1093/ajcn/76.1.281s
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index and obesity,,,

Abstract: Although weight loss can be achieved by any means of energy restriction, current dietary guidelines have not prevented weight regain or population-level increases in obesity and overweight. Many high-carbohydrate, low-fat diets may be counterproductive to weight control because they markedly increase postprandial hyperglycemia and hyperinsulinemia. Many high-carbohydrate foods common to Western diets produce a high glycemic response [high-glycemic-index (GI) foods], promoting postprandial carbohydrate oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
380
0
18

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 535 publications
(414 citation statements)
references
References 31 publications
7
380
0
18
Order By: Relevance
“…The increased prevalence of overweight in Western societies has been associated with higher intake of refined sugars and fat (Drewnowski et al, 1982;Drewnowski, 1997;Astrup, 2001;Nasser, 2001;Brand-Miller et al, 2002). Besides metabolic and lifestyle reasons, a difference in taste and smell perception between obese and normal-weight individuals has been suggested to cause differences in food choice and energy consumption (Drewnowski et al, 1995;Drewnowski, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The increased prevalence of overweight in Western societies has been associated with higher intake of refined sugars and fat (Drewnowski et al, 1982;Drewnowski, 1997;Astrup, 2001;Nasser, 2001;Brand-Miller et al, 2002). Besides metabolic and lifestyle reasons, a difference in taste and smell perception between obese and normal-weight individuals has been suggested to cause differences in food choice and energy consumption (Drewnowski et al, 1995;Drewnowski, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to obesity that has reached to epidemic proportions, the efficacy of low-fat diets has been questioned in recent years and instead the hypothesis has been focused on the intake of high-GI foods (Ludwig, 2000;Brand-Miller et al, 2002;Pawlak et al, 2002). Various studies have demonstrated positive acute effect of low-GI food, for example, increased satiety in healthy subjects (Granfeldt et al, 1994;Liljeberg and Björck, 1998;Ö stman et al, 2005) and decreased voluntary food intake in obese subjects (Ludwig, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The classification of foods according to their glycaemic response has been used in the management of diabetes mellitus, dyslipidaemia and excess body weight (Jenkins et al, 1981(Jenkins et al, , 1985Brand-Miller et al, 2002). Consumption of foods with a lower glycaemic response have been promoted to have a number of putative health benefits including promotion of long-term weight loss by influencing satiety and food intake and reduced glucose and insulin responses (Lavin and Read, 1995;Ludwig, 2000).…”
Section: Introductionmentioning
confidence: 99%